1986
DOI: 10.1177/014107688607901012
|View full text |Cite
|
Sign up to set email alerts
|

Indications for and Results of Operation in Inflammatory Bowel Disease

Abstract: Of 363 patients with inflammatory bowel disease presenting between 1972 and 1983, 166 required definitive operation. A classification by histological type distinguishes Crohn's disease (CD) from ulcerative colitis (UC) and indeterminate inflammatory bowel disease. CD is divided into predominantly ileal disease (81), total or subtotal colonic disease (74) and distal disease (22), whilst UC is classified into colonic (95) or distal disease (63). Most patients with ileal disease required operation for chronic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…In CD patients, the highest rate of surgery was for inflammation of the small bowel, with 80% of cases requiring at least one operation. This finding coincides with results reported by Schofield et al (7), who reported an operation rate of 86%. Analysis of the data from our study shows that CD is much more likely than UC to require surgery and that, of the different disease locations of CD, surgery seems to be performed least frequently for distal colonic involvement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In CD patients, the highest rate of surgery was for inflammation of the small bowel, with 80% of cases requiring at least one operation. This finding coincides with results reported by Schofield et al (7), who reported an operation rate of 86%. Analysis of the data from our study shows that CD is much more likely than UC to require surgery and that, of the different disease locations of CD, surgery seems to be performed least frequently for distal colonic involvement.…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of CD and UC in the gastrointestinal tract only in part mirrored the published results (4,7). In CD patients, the small number of distal colitis cases was consistent with results found by Schofield et al 7, who found only 12.5% of CD inflammation to be distal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Colocolonic anastomoses, however, did worse compared with other anastomoses; this accords with previous findings. [23][24][25] Earlier history of postoperative IASC and number of previous laparotomies for CD did not affect the outcome. Patients operated on more than once during the study were prone to suffer from more aggressive CD and also received AZA/6-MP more frequently.…”
Section: Discussionmentioning
confidence: 99%